Estimating the impact of stroke unit care in a whole population: an epidemiological study using routine data. Issue 12 (2nd July 2010) - Langhorne, Peter; Lewsey, James D; Jhund, Pardeep S; Gillies, Michelle; Chalmers, Jim W T; Redpath, Adam; Briggs, Andrew; Walters, Matthew; Capewell, Simon; McMurray, John J V; MacIntyre, Kate
Abstract : Background and purpose: Randomised trials indicate that organised inpatient (stroke unit) care has an important impact on patient outcomes with an absolute risk difference (ARD) of 3% for survival and 5% for returning home. However, it is unclear what impact this complex intervention actually has in routine practice. A comprehensive national dataset was used to study the impact of stroke unit implementation. Methods: The Scottish linked discharge database was used to identify all patients admitted to hospital with an incident stroke. Analyses compared case fatality and discharge home (adjusted for age, sex, deprivation and comorbidity) for hospitals with or without a stroke unit during four consecutive study periods: 1986–1990, 1991–1995, 1996–2000 and 2001–2005. Results: During the study period, the percentage of admissions to hospitals that had a stroke unit increased from 0% to 87%, the 6 month case fatality decreased from 45% to 29% and discharges home increased from 46% to 59%. Adjusted ORs (95% CI) for case fatality (stroke unit versus no unit) in each study period were as follows: not calculable (no units before 1991), 0.83 (0.78–0.89), 0.90 (0.86–0.94) and 0.87 (0.82–0.91). These equate to an ARD of 3.0% over the whole study period. Equivalent data for discharge home indicated an increased odds of discharge home: not calculable, 1.23 (1.15–1.31), 1.15 (1.10–1.21) and 1.17 (1.11–1.23) with an overall ARD of 5%. Conclusions: These results indicate a positive impact of a policy of stroke unit care on case fatality and discharge home. The estimated impact, after adjusting for case mix, appears very similar to that calculated using clinical trial data.